EVALUASI PENILAIAN LOKASI PELEDAKAN SEBAGAI INDIKATOR PENGENDALIAN RISIKO DAN BAHAYA DI AREA PIT SUBAN JERIJI SELATAN DAN PIT BANKO TENGAH BLOK A PT BUKIT ASAM Tbk, TANJUNG ENIM, SUMATERA SELATAN - Bella Puteri Ramadhani; Suhaediman Gumanti; Ridho Yovanda (Jurnal Humaniora & Sosial Sains, 2025)
This study discusses blasting activities, which are a crucial stage in hard rock mining, because they are effective in demolition but also pose high risks to the safety of workers, equipment, and the environment. This study evaluates blasting site assessments as risk control indicators in two mining areas of PT Bukit Asam Tbk, namely the Suban Jeriji Selatan (SJS) Pit and Banko Tengah Block A (BTA) in Tanjung Enim, South Sumatra. The method used is a qualitative approach through direct field observation, including the use of assessment forms and data collection of blasting equipment. The evaluation is carried out using a scoring system, where the maximum total score is 300 points indicating safe conditions if achieved. The results show that in the SJS Pit, 7 locations were evaluated and 35% of them managed to obtain scores above 270 points, indicating that the area is overall safe for blasting activities. This study also refers to the Decree of the Minister of Energy and Mineral Resources Number 1827 K / 30 / MEM / 2018 concerning Good Mining Engineering Principles, as a reference for implementing safety standards in blasting activities.